C programming for the PIC microcontroller : demystify coding with embedded programming - Ward, Hubert Henry (Apress L.P., 2020)
Go beyond the jigsaw approach of just using blocks of code you don't understand and become a programmer who really understands how your code works. Starting with the fundamentals on C programming, this book walks you through where the C language fits with microcontrollers. Next, you'll see how to use the industrial IDE, create and simulate a project, and download your program to an actual PIC microcontroller. You'll then advance into the main process of a C program and explore in depth the most common commands applied to a PIC microcontroller and see how to use the range of control registers inside the PIC. With C Programming for the PIC Microcontroller as your guide, you'll become a better programmer who can truly say they have written and understand the code they use. You will: Use the freely available MPLAX software Build a project and write a program using inputs from switches Create a variable delay with the oscillator source Measure real-world signals using pressure, temperature, and speed inputs Incorporate LCD screens into your projects Apply what you've learned into a simple embedded program.